Is God a mathematician? - Livio, Mario, 1945- (New York : Simon & Schuster Paperbacks, 2010)
Explores how various mathematical theories and discoveries have offered deeper insight into the universe, demonstrating the link between the scientific world and the human mind.
A mystery -- Mystics : the numerologist and the philsopher -- Magicians : the master and the heretic -- Magicians : the skeptic and the giant -- Statisticians and probabilists : the science of uncertainty -- Geometers : future shock -- Logicians : thinking about reasoning -- Unreasonable effectiveness? -- On the human mind, mathematics, and the universe.
Includes bibliographical references (p. [253]-291) and index.
Booklist starred
Library Journal
Publisher's Weekly
Booklist starred, December 2008
Kirkus Review, November 2008
Keywords: Discoveries in science; Logic, Symbolic and mathematical; Mathematicians -- Psychology; Mathematics -- Philosophy; Discoveries in science; Mathematicians -- Psychology; Mathematics -- Philosophy; Symbolic logic